Medieval brick and stone timber framed houses – a missing link in the development of Silesian tenement house? - Mruczek, Roland (Archaeologia Historica Polona, 2020)
Our study presents the most recent directions of research on the medieval burgher house in Silesia, looking at the issue through the prism of a certain house from Głogów, unique in the region, with a mixed brick and timber-framed structure with Steinwerk, which forces us to ask questions about the universality of this type of solutions – long absent in the panorama of large Silesian cities. A proposition of the typology of Silesian townhouses with a mixed structure, which was based on the results of research conducted by the author in Silesian cities in the years 1997–2018, was also presented.